Testing photogrammetry-based techniques for three-dimensional surface documentation in forensic pathology - Urbanová, Petra; Hejna, Petr; Jurda, Mikoláš (Forensic science international, 2015)
Three-dimensional surface technologies particularly close range photogrammetry and optical surface scanning have recently advanced into affordable, flexible and accurate techniques. Forensic postmortem investigation as performed on a daily basis, however, has not yet fully benefited from their potentials. In the present paper, we tested two approaches to 3D external body documentation - digital camera-based photogrammetry combined with commercial Agisoft PhotoScan(®) software and stereophotogrammetry-based Vectra H1(®), a portable handheld surface scanner. In order to conduct the study three human subjects were selected, a living person, a 25-year-old female, and two forensic cases admitted for postmortem examination at the Department of Forensic Medicine, Hradec Králové, Czech Republic (both 63-year-old males), one dead to traumatic, self-inflicted, injuries (suicide by hanging), the other diagnosed with the heart failure. All three cases were photographed in 360° manner with a Nikon 7000 digital camera and simultaneously documented with the handheld scanner. In addition to having recorded the pre-autopsy phase of the forensic cases, both techniques were employed in various stages of autopsy. The sets of collected digital images (approximately 100 per case) were further processed to generate point clouds and 3D meshes. Final 3D models (a pair per individual) were counted for numbers of points and polygons, then assessed visually and compared quantitatively using ICP alignment algorithm and a cloud point comparison technique based on closest point to point distances. Both techniques were proven to be easy to handle and equally laborious. While collecting the images at autopsy took around 20min, the post-processing was much more time-demanding and required up to 10h of computation time. Moreover, for the full-body scanning the post-processing of the handheld scanner required rather time-consuming manual image alignment. In all instances the applied approaches produced high-resolution photorealistic, real sized or easy to calibrate 3D surface models. Both methods equally failed when the scanned body surface was covered with body hair or reflective moist areas. Still, it can be concluded that single camera close range photogrammetry and optical surface scanning using Vectra H1 scanner represent relatively low-cost solutions which were shown to be beneficial for postmortem body documentation in forensic pathology.
Keywords: fotogrammetrie; zobrazování trojrozměrné; Male; Optical surface scanning; Point cloud comparison; Computer Simulation; Adult; Forensic Pathology; dospělí; mužské pohlaví; Imaging, Three-Dimensional; Software; algoritmy; Postmortem documentation; lidé; ženské pohlaví; Humans; soudní patologie; Algorithms; počítačová simulace; software; Female; lidé středního věku; Photogrammetry; Middle Aged